Ectopic third molar as a cause of sinusitis - Monti, Lira Marcela; Souza, Josué Gomes de; Pires Soubhia, Ana Maria; Gaetti Jardim-Junior, Elerson (ARCHIVES OF HEALTH INVESTIGATION, 2014)
Ectopic third molar teeth are those that are impacted in unusual positions, or that have been displaced and are at a distance from their normal anatomic location. Ectopic eruption of a tooth within the oral cavity is common, but rare in other sites. Ectopic eruption can be associated with developmental disturbances, pathologic processes or iatrogenic activity. Male, 19- years old, with an upper left ectopic third molar located in the maxillary sinus infraorbital region. The patient reported a bad taste and recurrent sinusitis that had been resistant to treatment. Surgical excision was carried out of the third molar tooth using the Caldwell-Luc approach. Keywords: Sinusitis; Third molar; Pathology, Infraorbital region.